Interaction between permafrost and infrastructure along the Qinghai–Tibet Railway detected via jointly analysis of C- and L-band small baseline SAR interferometry - Chen, Fulong; Lin, Hui; Li, Zhen; Chen, Quan; Zhou, Jianmin (Remote sensing of environment, 2012)
The Qinghai–Tibet Railway (QTR) is the highest and longest plateau linear structure in the world. The embankment is prone to instability, primarily due to the freezing and thawing of the permafrost overlying active layer. The infrastructure construction changes environmental conditions and in turn has influenced permafrost evolutions. In this study, we have investigated the feasibility of extracting surface motions in permafrost regions by means of satellite SAR interferometry. The relationship between surface deformation, permafrost active layer and other environmental conditions were further analyzed. In total, 19 L-band ALOS PALSAR SLC images (acquired from 21 June 2007 to 30 December, 2010) and 38 C-band Envisat ASAR SLC images (acquired from 18 November 2004 to 17 December, 2009) were employed to cover the Beiluhe experimental site, Qinghai, China. A hybrid persistent scatterer interferometry model based on interferometric point target analysis (IPTA) and small baseline strategy was firstly developed for surface motion estimation, minimizing the seasonal decorrelation effect. Then, the results from C- and L-band data were analyzed and compared, based on a statistical calibration model. Ground leveling data acquired from Fenghuo Mount Tunnel front with a one month interval were used for InSAR-derived results validation, revealing good agreement in displacement rates as well as time series. The QTR has been in operation since 2006. Our study has observed distinct surface motions along the embankment, primarily in the range of −20 to +20mm/yr, implying the necessity of continued satellite-based surveillance along the QTR. ► We monitor the surface motion along Qinghai–Tibet Railway by C- and L-band InSAR. ► The interaction between permafrost and infrastructure is analyzed. ► A persistent scatterer interferometry model is developed for surface motion inversion. ► The results are further validated by the ground measurements. ► This study implies the necessity for continued monitoring along the QTR.